The Purpose of the Tax System that Gives Meaning and Legitimacy to Taxes - Muñoz López, José Luis (Journal of Finance and Financial Law, 2022)
The purpose of this article is to analyze the ultimate purpose of the tax system that gives meaning and legitimacy to taxation. The citizen thus becomes an integral part of the State, has the ability to elect its representatives through suffrage. The law is a guarantee of equality and justice that provides legal security, facilitating peace and coexistence. This guarantee is manifested through the constitutional system (Alvarado Plana, 2016: 193–195), where the Constitution (Escudero, 2012: 857–858) becomes the legislative framework and the supreme norm of the entire legal system that orders the coexistence of citizens and ensures the proper functioning of the State. The tax system is defined as a revenue collection tool to cover the needs of the State, but there is certainly more than that: to achieve the goal of equality, justice, freedom, peace and well-being of the society, but also to guarantee the sustainability of the system, achieve progress and social peace. It is also essential to attract investment, create wealth and achieve proper development within the European Union (Sampedro, 2010: 300–309). Methodology. The analysis includes the basic values and principles assumed by Spanish culture, the evolution towards a modern society in which the citizen has rights and duties enshrined in the Constitution that justifies and legitimizes tax system and therefore taxes and a critical vision and an approach to our tax model through its ultimate purpose to contribute to defray public spending. All of these based on the principles and values established in the Spanish Constitution, which enshrines the rights of the citizen and, through them, supports the conception of the State itself. It also provides a modern approach to the future of our society and guarantees the legitimacy of our tax system. The result of the research. The analysis shows that the ultimate goal of the tax system is to contribute to public spending by the State. Therefore, in the contribution and control of spending, we find the guarantee that the State has healthy public accounts (deficit reduction, less public debt, and strict control of spending), so that the State has greater sovereignty and economic decision-making capacity. It allows the country to meet the objectives of the Constitution for any advanced society, such as peace, equality, justice, freedom and well-being of its citizens.